1979
DOI: 10.1002/1097-0142(197904)43:4<1418::aid-cncr2820430431>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Relation of pancreatic duct hyperplasia to carcinoma

Abstract: In order to find a relationship between ductal hyperplasia and carcinoma of the pancreas, histological and histochemical examinations were made on pancreatic specimens of 1,174 autopsy patients with special attention to the age incidence of the former. Ductal hyperplasia was divided into 3 types; nonpapillary, papillary, and atypical hyperplasia. All three types of hyperplasia and ductal carcinoma showed a similar tinctorial property in mucous histochemistry. In general, atypical hyperplasia was seen in the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
115
2
3

Year Published

1983
1983
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 291 publications
(128 citation statements)
references
References 8 publications
8
115
2
3
Order By: Relevance
“…The 5% sensitivity of our assay combining denaturing gradient gel electrophoresis and direct sequencing on PCR-amplified material is sufficient for (29) our samples containing either a single cell or two to three cells. The lower percentage of mutations in our study most likely is due to the selection of the samples because we excluded atypical papillary hyperplasia (i.e., severe ductal dysplasia), 16 which is associated with a high percentage of mutations as shown by Lemoine et al 18 and Moskaluk et al 21 The most commonly observed type of lesion in our study was mucinous cell hypertrophy (42%), also known as simple hyperplasia, 23 followed by ductal papillary hyperplasia (30%), adenomatoid hyperplasia (10%), and squamous metaplasia (4%). This proportional distribution generally confirms the results of other investigations.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The 5% sensitivity of our assay combining denaturing gradient gel electrophoresis and direct sequencing on PCR-amplified material is sufficient for (29) our samples containing either a single cell or two to three cells. The lower percentage of mutations in our study most likely is due to the selection of the samples because we excluded atypical papillary hyperplasia (i.e., severe ductal dysplasia), 16 which is associated with a high percentage of mutations as shown by Lemoine et al 18 and Moskaluk et al 21 The most commonly observed type of lesion in our study was mucinous cell hypertrophy (42%), also known as simple hyperplasia, 23 followed by ductal papillary hyperplasia (30%), adenomatoid hyperplasia (10%), and squamous metaplasia (4%). This proportional distribution generally confirms the results of other investigations.…”
Section: Discussionmentioning
confidence: 60%
“…This proportional distribution generally confirms the results of other investigations. 10,17,23,24 To study the spatial association between pancreatic ductal lesions and invasive ductal adenocarcinoma, we compared the frequency of ductal lesions adjacent to the tumors with their frequency at the tumor free resection margin that was at a distance of at least 1 cm from the tumor. This examination revealed that, irrespective of type, the lesions were distributed evenly in adjacent and remote tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, many studies have shown an association between pancreatic adenocarcinoma and intraductal neoplasia (6,7,9). PanIN has been estimated to occur commonly in patients without a history of pancreatic cancer in autopsy samples and in pancreatic tissue removed for nonneoplastic disease, with different studies having a prevalence of around 20 to 30%, though it is considerably more frequent in patients with carcinoma (6,7,8,21). High-grade PanIN occurs only rarely in patients without a history of pancreatic neoplasia (6,7).…”
Section: Discussionmentioning
confidence: 99%
“…Like all epithelial malignancies, pancreatic cancer arises from non-invasive precursor lesions after a prolonged series of stepwise progressions. [11][12][13][14] Almost 100 years ago, Hulst noted many transitional forms between normal pancreatic ductal epithelium and invasive cancer. 11 He suggested that the first change was a simple cellular hypertrophy, the second involved acquisition of a papillary architecture, and the last was an irregular growth of epithelium very similar to cancer.…”
Section: How Does One Get a Pancreatic Cancer?mentioning
confidence: 99%